2019
DOI: 10.3390/brainsci9110306
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Symptoms among African-American Older Adults in Economically Disadvantaged Areas of South Los Angeles

Abstract: Background. Although psychosocial and health factors impact insomnia symptoms, less is known about these effects in economically disadvantaged African-American older adults. Aims. This study investigated social and health determinants of insomnia symptoms among economically disadvantaged African-American older adults. Methods. This survey enrolled 398 African-American older adults (age ≥ 65 years) from economically disadvantaged areas of South Los Angeles. Gender, age, educational attainment, financial difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
10
0
1
Order By: Relevance
“…This community-based cross-sectional study surveyed a convenience sample (n = 740) of older African Americans residing in South Los Angeles [3,4,6,[28][29][30][31]. Also referred to as "South Los Angeles" Service Planning Area 6 of Los Angeles County, which serves the communities of Athens, Compton, Crenshaw, Florence, Hyde Park, Lynwood, Paramount, and Watts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This community-based cross-sectional study surveyed a convenience sample (n = 740) of older African Americans residing in South Los Angeles [3,4,6,[28][29][30][31]. Also referred to as "South Los Angeles" Service Planning Area 6 of Los Angeles County, which serves the communities of Athens, Compton, Crenshaw, Florence, Hyde Park, Lynwood, Paramount, and Watts.…”
Section: Methodsmentioning
confidence: 99%
“…This subset of older adults is faced with numerous health disparities, including lower rates of preventative health services and a greater delay in care. Individuals enrolled in any type of nursing facility, enrolled in any other research study, and who have observable intellectual impairments, were excluded from this study [3,4,6,[28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor quality of sleep not only seriously affects the quality of life ( Wang F. et al, 2019 ) but also leads to serious psychosomatic problems (e.g., loneliness and cognitive impairment) among Chinese elders ( Suh et al, 2018 ; Yu et al, 2018 ). Long-term insomnia would lead to a decline in body function as well as an increase in the risk of various mental disorders, physical illnesses, and mortality ( Bazargan et al, 2019 ). However, most of the current research made concerns on the general elders.…”
Section: Introductionmentioning
confidence: 99%
“…In general, older people tend to go to sleep earlier and wake earlier than younger adults for a number of different reasons, such as insomnia and sleep apnea, which are the most common sleep problems among older people [42]. A survey in older African-American people from disadvantaged financial areas of South Los Angeles revealed that insomnia symptoms co-exist with many mental, physical, and financial challenges and that sleep could be one of the ways to cope with these challenges [43]. Sleep apnea can also cause other problems as well, such as memory loss, high blood pressure, or even stroke [44], and all of these problems affect the quality of life of older people, their sleep duration, and therefore their course of aging.…”
Section: Discussionmentioning
confidence: 99%